Analysis and Perspectives on the Required Competencies for Students at the National University of Chimborazo in the Management Programme, Ecuador - Liccioni , Edith Josefina; Salas, Francisco Paul Pérez; Alberto , Bravo Hidrovo Nicky; Fabricio , Benítez Obando Iván; Mora , Omar Flor Patricio (Journal of Ecohumanism, 2024)
The study analyses the essential competencies for Business Administration students, emphasising their relevance in training competitive professionals for a globalised and dynamic labour market. Using a mixed methodology based on Kurt Lewin's Action Research Theory, participatory workshops, questionnaires, and semi-structured interviews were employed to collect data from a sample of 52 students. The analysis involved statistical techniques and thematic categorisation to identify patterns and trends. Twenty-four key competencies were identified, grouped into technical, methodological, social, and personal categories. In technical competencies, digital literacy (85%) and digital skills (90%) stood out for their importance in technological adaptation, while big data analysis (60%) indicated an area for improvement. Among methodological competencies, critical thinking (80%), problem-solving (88%), and analytical skills (82%) were deemed essential for decision-making. In social competencies, teamwork (95%) and leadership (72%) were highlighted as fundamental. Finally, in personal competencies, ethics (80%) and continuous learning (85%) emerged as pillars of professional development. The study concludes that while social and technical competencies are highly valued, areas such as data analysis and networking require greater curricular emphasis to produce more well-rounded and adaptable professionals